Low acid hydrothermal fractionation of Giant Miscanthus for production of xylose-rich hydrolysate and furfural. (October 2016) - Kim, Tae Hyun; Ryu, Hyun Jin; Oh, Kyeong Keun
Highlights: LAH (low acid hydrothermal) fractionation process was optimized. Xylan degradation, xylose recovery, and xylose decomposition were evaluated. Furfural production rate was high at early LAH fractionation stage, then decreased. Xylose-rich hydrolyzate and glucan-rich residual solid were obtained. Abstract: Low acid hydrothermal (LAH) fractionation was developed for the effective recovery of hemicellulosic sugar (mainly xylose) from Miscanthus sacchariflorus Goedae-Uksae 1 ( M . GU-1). The xylose yield was maximized at 74.75% when the M . GU-1 was fractionated at 180 °C and 0.3 wt.% of sulfuric acid for 10 min. At this condition, the hemicellulose (mainly xylan) degradation was 86.41%. The difference between xylan degradation and xylose recovery yield, i.e., xylan loss, was 11.66%, as indicated by the formation of decomposed products. The furfural, the value added biochemical product, was also obtained by 0.42 g/L at this condition, which was 53.82% of furfural production yield based on the xylan loss. After then, the furfural production continued to increase to a maximum concentration of 1.87 g/L, at which point the xylan loss corresponded to 25.87%.